A literature Review on the Effects of Islam on Entrepreneurship in Muslim Countries; with focus on Iran (Global Journal of Human-Social Science, 2012)
This paper aims to explore the Entrepreneurship in general Islamic entrepreneurship and also Iran will be studied as a Muslim country
Keywords: Entrepreneurship; Entrepreneurship in Islam; wealth in Islam; Iran